THE ASCENDANCY OF ARTIFICIAL INTELLIGENCE: A PARADIGM SHIFT IN MODERN SOCIETY (International Journal of Food and Nutritional Sciences, 2022)
The proliferation of Artificial Intelligence (AI) has precipitated a transformative era in human history, revolutionizing the fabric of modern society. This article delves into the burgeoning phenomenon of AI adoption, examining the multifaceted implications of its increased use across various sectors. Through a comprehensive analysis of empirical data and expert insights, this study elucidates the profound impact of AI on industries, economies, and individual lives. The findings reveal a paradigm shift in the way we live, work, and interact, as AI assumes a pivotal role in driving innovation, enhancing productivity, and redefining the boundaries of human potential. Furthermore, the article explores the concomitant challenges and concerns surrounding AI's ascendancy, including issues of job displacement, ethical considerations, and the imperative for responsible AI development. Ultimately, this research underscores the imperative for a nuanced understanding of AI's transformative power and its far-reaching consequences, as humanity navigates the uncharted territories of an AI-driven future.